AI-GENERATED LEARNING RESOURCES FOR CREATIVE FIELDS - Jadhav, Kunal Dhaku; Narayana, Ananta; Chaudhari, Leena Bharat; Monisha J.; Ambhore, Vishal; Shelke, Ganesh Chandrabhan (ShodhKosh: Journal of Visual and Performing Arts, 2026)
With the rapid development of artificial intelligence, the production and distribution of educational material have changed, especially in such creative industries as art, design, music, media, and architecture. The paper explores how AI-generated learning tools can be used to improve creative education through offering adaptive, multimodal, and personalized teaching resources. In contrast to more conventional tools of a static nature, generative AI systems have the capability to create tutorials, design prompts, visual exemplars, musical exercises, and reflective critiques in a dynamic fashion based on the profile of a specific learner. The article can be seen to provide a well-developed conceptual framework based on the advances in artificial intelligence in education, generative models, and creativity-support tools to describe how AI may support the development of technical skills as well as creative exploration. A system architecture that is modular is suggested, which includes creative knowledge repositories, model training/fine-tuning pipelines, and personalization mechanisms that occur based on the learner behavior and performance data. The methodology specifies the combination of quantitative measures of learning effectiveness and creativity with the qualitative user studies with the involvement of students and educators associated with various creative fields. The need to compare results shows that the engagement, conceptual knowledge, and efficiency of practice have increased and can be measured when AI-generated resources are used in addition to traditional teaching resources. Nevertheless, it is also possible to note that the study critically analyzes such issues as the alignment of the pedagogy, its quality assurance, the cultural bias, and the threat of over-reliance on the auto-generation of the content.